'An endless procession of catastrophes': Reading the War on Terror in Contemporary HIV Life Writing. (August 2020) - Zapasnik, Jonathon
Abstract : This paper examines the shifting paradigms of language used in HIV/AIDS life writing. As a testimonial genre, military metaphors have played a crucial role in mobilising communities and revealing how discourses around chronic illness inscribe themselves on the body. Through a textual analysis of three memoirs, Douglas Wright's Ghost Dance (2004) and Terra Incognito (2006), and David Caron's The Nearness of Others (2014), I argue that these texts represent a shift that instead engage metaphors of terrorism and security to convey meaning of lived experience and negotiate the precariousness of ongoing survival. Simultaneously, Wright and Caron maintain their health through protease inhibitors and reflect on the national anxieties produced by the September 11 terrorist attacks in the United States of America. Both writers draw on the language of terrorism, especially the images taken from the Abu Ghraib prison, to inform their own experiences as HIV-positive white, middle-upper class, gay men. The significance of these metaphors can be found in their individual struggles with depression. What this paper contributes to is an understanding of what it means to think about HIV after the pharmaceutical turn when HIV is no longer considered a death sentence in the Western world, how discourses of terror inform public and personal understandings of chronic illness and mental health, and how embodied experience informs autobiographical modes of expression, and vice versa.